The Screwtape Letters/ Study guide - Poteet, Michael (Fall Creek,WI. Progeny Press, 2001)
Progeny Press Study Guides provide teachers, parents, and students with literary analysis based upon the foundation of the Bible. Examining well-written literature in relation to biblical standards, students will develop and refine how they deal with man's philosophies while learning about the craft of writing. Progeny Press study guides deal with literature as works of art and philosophy as they explain and use literary terms; deal with plot construction; dig into character studies; and bring attention to themes and ideas the author has crafted.